Gut microbiome and blood glucose control in type 1 diabetes: a systematic review - Abuqwider, Jumana; Corrado, Alessandra; Scidà, Giuseppe; Lupoli, Roberta; Costabile, Giuseppina; Mauriello, Gianluigi; Bozzetto, Lutgarda (Frontiers in Endocrinology, 2023)
Objective The risk of developing micro- and macrovascular complications is higher for individuals with type 1 diabetes (T1D). Numerous studies have indicated variations in gut microbial composition between healthy individuals and those with T1D. These changes in the gut ecosystem may lead to inflammation, modifications in intestinal permeability, and alterations in metabolites. Such effects can collectively impact the metabolic regulation system, thereby influencing blood glucose control. This review aims to explore the relationship between the gut microbiome, inflammation, and blood glucose parameters in patients with T1D. Methods Google Scholar, PubMed, and Web of Science were systematically searched from 2003 to 2023 using the following keywords: “gut microbiota,” “gut microbiome,” “bacteria,” “T1D,” “type 1 diabetes,” “autoimmune diabetes,” “glycemic control,” “glucose control,” “HbA1c,” “inflammation,” “inflammatory,” and “cytokine.” The examination has shown 18,680 articles with relevant keywords. After the exclusion of irrelevant articles, seven observational papers showed a distinct gut microbial signature in T1D patients. Results This review shows that, in T1D patients, HbA1c level was negatively correlated with abundance of Prevotella, Faecalibacterium, and Ruminococcaceae and positively correlated with abundance of Dorea formicigenerans, Bacteroidetes, Lactobacillales, and Bacteriodes. Instead, Bifidobacteria was negatively correlated with fasting blood glucose. In addition, there was a positive correlation between Clostridiaceae and time in range. Furthermore, a positive correlation between inflammatory parameters and gut dysbiosis was revealed in T1D patients. Conclusion We draw the conclusion that the gut microbiome profiles of T1D patients and healthy controls differ. Patients with T1D may experience leaky gut, bacterial translocation, inflammation, and poor glucose management due to microbiome dysbiosis. Direct manipulation of the gut microbiome in humans and its effects on gut permeability and glycemic control, however, have not been thoroughly investigated. Future research should therefore thoroughly examine other potential pathophysiological mechanisms in larger studies.